2021
DOI: 10.1177/00957984211021236
|View full text |Cite
|
Sign up to set email alerts
|

Remixing the Script? Associations Between Black-Oriented Media Consumption and Black Women’s Heteropatriarchal Romantic Relationship Beliefs

Abstract: Black-oriented media may offer Black women an opportunity to produce and consume empowering messages that challenge heteropatriarchal relationship beliefs, but they may also foster their endorsement. Drawn by this paradox, we surveyed 597 undergraduate and graduate Black women aged 18 to 30 years to examine exposure to Black-oriented media and their association with the acceptance of heteropatriarchal relationship beliefs. Correlation and regression analyses showed that reading more Black magazines was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Despite the risks of increased racial discrimination, digital media has been identified as a notable site where socialization occurs for Black youth (Anyiwo et al, 2021; Avery et al, 2021; Boulianne, 2020; Chan, 2017). Black youth utilize social media to engage around topics of importance to them and to voice opinions, both passively (e.g., simply posting, liking, or viewing) and actively (i.e., engaging in exchanges with others, content creation).…”
Section: Prsmentioning
confidence: 99%
“…Despite the risks of increased racial discrimination, digital media has been identified as a notable site where socialization occurs for Black youth (Anyiwo et al, 2021; Avery et al, 2021; Boulianne, 2020; Chan, 2017). Black youth utilize social media to engage around topics of importance to them and to voice opinions, both passively (e.g., simply posting, liking, or viewing) and actively (i.e., engaging in exchanges with others, content creation).…”
Section: Prsmentioning
confidence: 99%
“…Much of the existing literature regarding sexual socialization from media sources centers around movies, music videos, social media, TV shows, and pornography. The findings of these studies varied depending upon media source, age of study, and research design, but a common theme was the reinforcement of stereotypes about Black women (e.g., Avery et al, 2021; Coyne, et al, 2019; Overbeek, et al, 2018; Seabrook et al, 2016; Ward et al, 2020). Seabrook et al (2016) and Avery et al (2021) reported that consuming high levels of reality television reinforced a heterosexual script in Black college-aged individuals.…”
Section: Perspectives For Understanding Sexual Socializationmentioning
confidence: 99%
“…The findings of these studies varied depending upon media source, age of study, and research design, but a common theme was the reinforcement of stereotypes about Black women (e.g., Avery et al, 2021; Coyne, et al, 2019; Overbeek, et al, 2018; Seabrook et al, 2016; Ward et al, 2020). Seabrook et al (2016) and Avery et al (2021) reported that consuming high levels of reality television reinforced a heterosexual script in Black college-aged individuals. These messages included women setting sexual limits and men highly valuing a woman’s physical appearance.…”
Section: Perspectives For Understanding Sexual Socializationmentioning
confidence: 99%